ROLE OF KANA KAJJALI IN THE MANAGEMENT OF AJEERNA (INDIGESTION): AN OPEN CLINICAL STUDY - Joshi, Namrata; Kumar Dash, *Manoj; Kumar Panda, Pradeep (International Journal of Ayurveda and Pharma Research, 2019)
Ajeerna (Indigestion) is the state of unfinished process of digestion of ingested food. Kana Kajjali is a classical formulation indicated in the treatment of Ajeerna. It is prepared by Kana (Piper longum)- a herbal drug and herbomineral preparation Kajjali (Black sulphide of mercury). In the present study, an effort has been made to assess the effect of herbomineral formulation Samaguna (Hg:S=1:1) Kana Kajjali and Shadadguna (Hg:S=1:6) Kana Kajjali (Black sulphide of Mercury with Piper longum)on indigestion. Materials and methods: The study was carried out on 83 patients of indigestion. Patients were divided into three groups with simple random sampling method: Group A was treated with Samaguna Kana Kajjali tablet at the dose of 125 mg; Group B was treated with Kana tablet 250 mg; while group C was treated Shadaguna Kana Kajjali tablet at the dose of 125 mg; twice a day after meal. Duration of the treatment was 10 days. Assessment was done on the basis grading of classical signs and symptoms of the disease with application of paired t- test. Results: Highly significant (p<0.001) effect was seen in Samaguna Kana Kajjali group on symptoms like Angamarda, Tiktoamlodgara and Shadguna Kana Kajjali on one Vataja symptom viz. Pravahanam and three Kaphaja symptom viz. Utlesha, Arochaka and Avipaka with best result with Shadguna Kana Kajjali especially on Kaphaja symptoms. Conclusion: Above study confirms that an increase in the concentration of Gandhaka in Parada enhances the therapeutic efficacy of the later drug.